The Empty Box Phenomenon in the 2024 Simultaneous Regional Elections: Democracy Challenge or People's Choice? - Febriandy, Radians Krisna; Rini Sudarmanti (Jurnal Spektrum Komunikasi, 2024)
The empty box phenomenon in the 2024 simultaneous regional elections is a representation of public dissatisfaction with the quality of candidates and political processes that characterize the local area. This study aims to explore the subjective experiences of voters who will vote for an empty box and the meaning behind their choice. This research uses a qualitative approach with phenomenological methods to find out the perceptions, motivations, and expectations of voters in areas with a single candidate. Interviews were conducted online with eleven (11) participants selected by purposive sampling with varied age, education, and economic backgrounds using Google Form application with ten (10) structured questions. The results of the study explain the main themes that emerged from the results of thematic analysis include distrust in the quality of candidates, blank votes as a form of protest against the political system, hope for fairer and more transparent elections, and finally social influence in making choices. The findings therefore suggest that this was a kind of protest, not only against one of the candidates, but also an expression of dissatisfaction with the dominance of the local ruling elite. Voters hope that this phenomenon can encourage changes to a more representative electoral system in the future.